"An In-vitro Evaluation of Effects of Light and Light-Heat Curing Inlay Composite Restorations on Fracture Resistance of Pulpless Maxillary Premolars " - M. Mousavinasab; S. Ashrafijoo (Tehran University of Medical Sciences, 2004)
Statement of Problem: The restoration of the teeth should have enough ability to withstand masticator forces while preserving as much tooth structure as possible. Purpose: The purpose of this study was to compare the effects of light-heat cured composite with light cured composite restorations on fracture resistance of the restored teeth. Materials and Methods: Forty healthy maxillary premolar teeth were chosen, endodontic treatment performed in 30 of them. MOD cavities were prepared in all of them to weaken tooth structures. Then, they were divided into 3 groups each of which contains 10 specimens. The groups were as follows: Group 1: unprepared teeth (sound teeth acted as control) Group 2: restored teeth with direct light cured composite resin. Group 3: restored teeth with light-heat cured composite resin as inlay without any cementing surface treatment Group 4: restored teeth with light-heat cured composite resin inlays with cementing surface treatment. Finally all samples were subjected to compressive load by testing machine. The data were analyzed using ANOVA and Duncan tests. Results: There was a significant difference in fracture resistance between 4 groups (P